14th International Symposium on Dentofacial Development and Function & 11th National Congress on Orthodontics Beijing, China, Sept. 19-23, 2012 (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
Abstract not availableBan J Orthod & Dentofac Orthop, April 2014; Vol-4 (1-2), P.35